Preparation of Case Method -Based Teaching Materials for Improving Learning Outcomes Students in the Course Knowledge Administration in the Administration Education Study Program Office Faculty of Economics State University of Medan - Pramana, Dodi; Sihombing, Dionisius; Armayanti, Nelly (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Development quality source Power man need education quality in line with need 21st century . Government has implement Independent Learning Policy For maximize potential student through experiential learning programs. However , in the Administration Education Study Program Office , minimal relevant teaching materials become constraints , where the lecturer Still use teacher -centered learning method with monotonous teaching materials , causing student not enough active in learning . Development teaching materials based on method case is very necessary For overcome limitations This . Case method based teaching materials can provide examples case real relevant​ with theory , so that help student in understand material , solve problems , and implement knowledge administration in a way practical . Research This aiming For analyze impact use case method based teaching materials in the course Knowledge Administration to results Study students . Research This using the ADDIE development model which includes stages of Analysis, Design, Development, Implementation, and Evaluation. Data analysis is carried out For measure validity , effectiveness , and practicality teaching materials . The results of study This expected produce relevant , effective and practical teaching materials For used in learning , as well as can registered as Copyright and IPR of books Knowledge Administration . Keywords : Teaching Materials, Learning Results , Knowledge Administration